BILINGUALISM AND STUTTERING: HOW BILINGUAL INDIVIDUALS ARE MORE PRONE TO STUTTERING - Shaharudin, Ilham Fatini Muhammad; Nizam, Nurin Maisarah Ahmad; Za’im, Nur’eisya Humayra Mohamad; Yahya, Siti Nur Najihah; Mahayudin, Nur Annisa Mohamad; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Stuttering is a complex speech disorder which affects millions of people worldwide, while bilingualism plays a significant role in affecting its presence and severity. Therefore, this paper attempts to critically examine the relationship between bilingualism and stuttering risk and severity, which is fulfilled by investigating how language proficiency, language dominance, and cognitive load influence speech fluency. Thus, the Dynamic Restructuring Model and the Dual Diathesis-Stressor model are used to provide insights into the interaction between bilingualism and stuttering, emphasizing the role of cortical regions as well as emotional and linguistic stressors in speech disfluencies. In integrating Islamic perspectives, the study highlights the importance of culturally sensitive and neurophysiologically informed approaches that align with neural and cognitive demands, as well as holistic well-being of individuals. Meanwhile, gaps and limitations mentioned in the current study include small sample sizes, inconsistent methodologies, and limited literature, which hinder the generalizability and applicability of findings. By addressing these gaps, this review aims to inform future research and enhance treatment approaches for bilingual individuals who stutter.